LANGUAGE SHIFT AND CULTURAL POLICING AMONG THE OGU OF SOUTHWESTERN NIGERIA (2017)
Language Shift Language Maintenance (LSLM) designates the investigation of movement patterns from one language to another and the efforts made by native speakers and institutions to reverse the shift. Ogu, a minority language in Southwestern Nigeria, had been experiencing shift to Yoruba and English. Existing literature on Ogu LSLM affirm shift without extensively acknowledging systematic strategies being adopted by native speakers in the maintenance of the language. This study, therefore, examined cultural policing as a unique maintenance strategy that the elite Ogu have adopted to stem the tide of the shift with a view to investigating its dynamics and efficacy. The study adopted Fishman’s Graded Intergenerational Disruption Scale (GIDS) to assess the extent of shift of Ogu, and Giles et al’s Ethnolinguistic Vitality Theory (EVT) to assess the extent to which Ogu people’s vitality has positively impacted on the language. Data were collected through participant observation and purposively through 12 key informant interviews with individuals involved in cultural policing: four in each local government area (LGA). Twelve in-depth interviews were conducted with four individuals who had been previously policed in each LGA. Three focus group discussions with native speakers in ancestral homelands were also held in Javie in Lagos State, Idi-Iroko and Obakobe in Ogun State. Data were content analysed. Ogu language experienced widespread shift to Yoruba and English, which manifested in the bearing of Yoruba names, speaking of Yoruba and the denial of Ogu identity. A reversal of attitude in favour of Ogu was facilitated by members of the Ogu community, identified as cultural police, who adopted informal non-coercive and subtle policing strategies as well as persuasion. The efficacy of the strategy rested substantially on the high formal education and cosmopolitan experience of the cultural police team. The feeling of linguistic nostalgia was engendered while the denial of Ogu identity in public was reduced. Efforts towards maintaining the language included intergenerational transfer, use of Ogu in domestic and public domains, reversion to Ogu names, sensitisation of the people into developing confidence in themselves and renewed loyalty to Ogu; all of which increased its ethnolinguistic vitality. Loyalty to Ogu was also tied to socio-economic benefits, namely: scholarships, bursaries, monetary gifts and job opportunities for Ogu speakers, which endeared the language to its people. Cultural policing was complemented with publishing of books in Ogu, translation of Yoruba and English hymns and songs to Ogu and encouragement of the Ogu in the Diaspora to pay regular visits to their ancestral homelands, particularly during festive periods. Ogu people have successfully initiated and ensured the maintenance of their language by employing subtle cultural policing strategies of persuasion and incentives. Cultural policing should be employed in efforts geared towards safeguarding minority languages